DISCOVERY OF MICROFILARIA IN MEXICAN BIRDS - BELTRAN, ENRIQUE (Rockefeller Foundation, CD MEXICO, DF, MEX, 1943)
The author redescribes Cephalogonimus americanus and makes some comments on Gorgoderina attenuata
REV SOC MEX HIST NAT
Keywords: DISCOVERY, MICROFILARIA, MEXICAN BIRDS; CIENCIAS DE LA VIDA; BIOLOGIA ANIMAL (ZOOLOGIA)